Intestinal permeation enhancers to improve oral bioavailability of macromolecules: reasons for low efficacy in humans. (1st February 2021) - Maher, Sam; Geoghegan, Caroline; Brayden, David J.
ABSTRACT: Introduction: Intestinal permeation enhancers (PEs) are substances that transiently alter the intestinal epithelial barrier to facilitate permeation of macromolecules with low oral bioavailability (BA). While a number of PEs have progressed to clinical testing in conventional formulations with macromolecules, there has been only low single digit increases in oral BA, irrespective of whether the drug met primary or secondary clinical endpoints. Areas covered: This article considers the causes of sub-optimal BA of macromolecules from PE dosage forms and suggests approaches that may improve performance in humans. Expert opinion: Permeation enhancement is most effective when the PE is co-localized with the macromolecule at the epithelial surface. Conditions in the GI tract impede optimal co-localization. Novel delivery systems that limit dilution and spreading of the PE and macromolecule in the small intestine have attempted to replicate promising enhancement efficacy observed in static drug delivery models.